Cervical Sagittal Alignment and Balance Associated With Aging Chinese Adults: A Radiographic Analysis - Jin, Linyu; Liang, Yan; Guo, Chen; Zheng, Bin; Liu, Haiying; Xu, Shuai (Global spine journal, 2024)
Study Design This was a retrospective cohort radiographic study. Objective To determine the age- and gender-related normative values and correlation of cervical sagittal parameters in asymptomatic Chinese adults, and to explore the changes and compensating mechanisms across different age groups. Methods The asymptomatic subjects were divided into 6 groups according to age and then one-way analysis of variance was used to compare the multiple sets of cervical sagittal parameters among the different age groups. Independent t-tests were performed to compare the sagittal parameters among different gender and different cervical spine alignments. Relationships between each parameter were tested by Pearson’s correlation. Linear regression analysis based on T1 slope (T1S) and C2 slope (C2S) was used to provide an equation to predict normal cervical alignment. Results Mean values of each cervical sagittal parameter were presented based on age and gender. There were positive correlations between age and cervical lordosis (CL) (r = -.278, P < .001), T1S (r = .271, P < .001), cervical sagittal vertical axis (cSVA) (r = .218, P < .001), C2-C4 Cobb angle (r = -.283, P < .001), horacic inlet angle (TIA) (r = .443, P < .001), and neck tilt (NT) (r = .354, P < .001). Older groups (aged >50 years) had greater T1 Slope, C2S, and TIA. The C2-C4 Cobb angle maintained a steadily increasing trend and significantly increased in the older adult groups (P < .05), while the C5-C7 Cobb angle was relatively constant. Mean values of parameters were larger in males (P > .05). Linear regression analysis indicated a strong association between T1S and CL (R2 = .551, standard error 1.16°), T1S and C5-7 (R2 = .372; P < .001), and C2S and C2-4 (R2 = .309; P < .001). Conclusions Normative values of cervical sagittal parameters vary by age and sex. The CL, cSVA, and T1S, C2-4 Cobb angle changed with increasing age, and it can influence the recruitment of compensation mechanism. Normative CL of Chinese adults was predicted by the equation CL = T1S-14.7° ± 1.2°, which could serve as a reference when planning for cervical surgery.